Exposure to 4-methylimidazole as a food pollutant induces neurobehavioral toxicity in mother and developmental impairments in the offspring. (2nd October 2021) - Mehri, Fereshteh; Salimi, Ahmad; Jamali, Zhaleh; Kahrizi, Farzad; Faizi, Mehrdad
Abstract: 4-methylimidazole (4-MEI), is received to humans through the foods and other sources. We have investigated neurobehavioral and developmental toxicity of 4-MEI in mother and offspring in mice. Results in vivo, showed that 4-MEI (100, 200 and 300 mg/kg) can induce neurobehavioral toxicity in pregnant mice by abnormalities in the hippocampus and disrupt neurobehavioral functions. Observation on fetuses showed that 4-MEI induces abortion, decrease the weight and length of the fetus and pathological abnormalities. These results suggested 4-MEI induces neurobehavioral and developmental toxicity. It is hoped that these results will be helpful for awareness of humans which are exposed with 4-MEI.